THz: Research Frontiers for New Sources, Imaging and Other Advanced Technologies (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The THz region of the electromagnetic spectrum is a frontier research area involving application of many disciplines, from outdoor to indoor communications, security, drug detection, biometrics, food quality control, agriculture, medicine, semiconductors, and air pollution. THz research is highly demanding in term of sources with high power and time resolution, detectors, and new spectrometer systems. Many open questions still exist regarding working at THz frequencies; many materials exhibit unusual or exotic properties in the THz domain, and researchers need new methodologies to exploit these opportunities. This book contains original papers dealing with emerging applications, new devices, sources and detectors, and materials with advanced properties for applications in biomedicine, cultural heritage, technology, and space.